Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) Berbantuan Wordwall pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN 03 Pasar Amping Parak Kabupaten Pesisir Selatan (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the low learning outcomes of students in Civic Education learning. The purpose of this study is to describe the improvement of student learning outcomes in Civic Education learning using the Problem Based Learning model assisted by Wordwall in the fourth grade of elementary school. The research employed is a type of classroom action research (CAR) using two types of approaches, namely qualitative and quantitative approaches. This study was carried out in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. The subjects of this research are the classroom teacher and 20 fourth-grade students. Data was collected using tests, questionnaires, and observations and analyzed both quantitatively and qualitatively. The research results indicate an improvement. First, the average score of the teaching module in cycle I was 87.45%, increasing in cycle II to 95.8%. Second, the teacher's aspect in cycle I had an average of 74.95%, increasing in cycle II to 92.8%. Third, the students' aspect in cycle I had an average of 74.95%, increasing in cycle II to 92.8%. Fourth, the students' learning outcomes in cycle I had an average of 72.2, increasing in cycle II to 86.4. Therefore, it can be concluded that the Problem Based Learning (PBL) model assisted by Wordwall can improve students' learning outcomes in the Pancasila Education class at SDN 03 Pasar Amping Parak, Pesisir Selatan District.